(untitled) (Philological Studies, 2019)
The paper deals with corpus of Croatian and Bulgarian phrases with compo- nents «Dog» and «Cat». We analyse origins, motivation, semantics and their equivalence in both languages. The semantic analysis shows that phrases mostly refer to human character and behaviour.